Cost-Effectiveness and Cost?Benefit Analyses of Providing Menstrual Cups and Sanitary Pads to Schoolgirls in Rural Kenya - Masih A. Babagoli; Anja Benshaul-Tolonen; Garazi Zulaika; Elizabeth Nyothach; Clifford Oduor; David Obor; Linda Mason; Emily Kerubo; Isaac Ngere; Kayla F. Laserson; Rhiannon Tudor Edwards; Penelope A. Phillips-Howard (Women's Health Reports, 2022)
Objective: To analyze the relative value of providing menstrual cups and sanitary pads to primary schoolgirls. Design: Cost-effectiveness and cost?benefit analyses of three-arm single-site open cluster randomized controlled pilot study providing menstrual cups or sanitary pads for 1 year. Participants: Girls 14?16 years of age enrolled across 30 primary schools in rural western Kenya. Methods: Cost-effectiveness analysis was conducted based on the health effects (reductions in disability-adjusted life years [DALYs]) and education effects (reductions in school absenteeism) of both interventions. The health and education benefits were separately valued and compared with relative program costs. Results: Compared with the control group, the cost of menstrual cups was estimated at $3,270 per year for 1000 girls, compared with $24,000 for sanitary pads. The benefit of the menstrual cup program (1.4 DALYs averted, 95% confidence interval [CI]: ?4.3 to 3.1) was higher compared with a sanitary pad program (0.48 DALYs averted, 95% CI: ?4.2 to 2.3), but the health effects of both interventions were not statistically significant likely due to the limited statistical power. Using point estimates, the menstrual cup intervention was cost-effective in improving health outcomes ($2,300/DALY averted). The sanitary pad intervention had a cost-effectiveness of $300/student-school year in reducing school absenteeism. When considering improvements in future earnings from reduced absenteeism, the sanitary pad program had a net benefit of +$68,000 (95% CI: ?$32,000 to +$169,000). Conclusions: The menstrual cup may provide a cost-effective solution for menstrual hygiene management in low-income settings. This study outlines a methodology for future analyses of menstrual hygiene interventions and highlights several knowledge gaps that need to be addressed. Trial registration: ISRCTN17486946.